PLAGIARISM IN CREATING ACADEMIC BASED ARGUMENTATIVE ESSAY: THE STRATEGIES TO AVOID IT - Putri Maharani, Anak Agung (Institut Hindu Dharma Negeri Denpasar, 2018)
Through this paper, the strategies of avoiding plagiarism implemented by the participants were presented. There were 136 fifth semester students of English Language Education Study Program (hereafter, ELESP) in Mahasaraswati Denpasar University who willingly contributed to the research investigation. All of them enrolled the Writing IV course which mainly focuses on academic writing and plagiarism. To attain the data, an open-ended questionnaire was distributed which followed by interview and Focus Group Discussion (henceforward, FGD). The obtained data were analyzed by means of Interactive Model which involves data collection, data filter, data presentation, and verification. It was found that the students encompassed 4 strategies in the attempt to avoid plagiarism such as producing a thorough outline prior to drafting, using own words, citing: quoting, paraphrasing, and utilizing plagiarism checker. These strategies are categorized into 3 different divisions based on the period of applying them.